IMPROVING FIRST GRADE STUDENTS SKILLS IN WRITING NARRATIVE TEXT THROUGH CLUSTERING TECHNIQUE AT SMKN 1 BANGUN PURBA - Saputra, Joni; Antoni, Rivi; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
Learning English directed to determine the students skill to communicate well and correctly, both spoken and in writing. This research is action research, the purpose of this research is to improve students writing narrative skills. The result of this research showed that there are some improvement after getting the second cycle. There are 12,5 % students was in fair level, and 81,25 % students was in good level and 6,25 % students was in excellent level. The conclusion of this research is the students skill in writing narrative text in the good category. The suggestion for the teacher, The teacher should provide various techniques or materials for students to develop their ideas.